Emanuel Hausman (1923–2022) - Notley, R. Steven (The Biblical archaeology review, 2022)
Emanuel Hausman passed away in Jerusalem on January 18, 2022, two weeks before his 99th birthday. Although many BAR readers may not be familiar with his name, they doubtless are the beneficiaries of his life’s work through the publishing house Carta Jerusalem. Hausman was a pioneer in the historical cartography of the land of […]